REVIEW ON THERAPEUTIC EFFECTS MEDIATED BY OMEGA-3 FATTY ACIDS IN ALZHEIMER'S DISEASE - Aarti, Sati; Priyanka, Bhatt (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Alzheimer's disease (AD) is a neurodegenerative disorder with relevant unmet therapeutic needs. Both natural aging and AD have been associated with a significant decline in the Omega-3 polyunsaturated fatty acid, docosahexaenoic acid (DHA), and accordingly, administration of DHA has been proposed as a possible treatment for this pathology. DHA and its derivatives like 2-hydroxy DHA-(OHDHA) have a strong therapeutic potential to treat AD. Studies have demonstrated that DHA induced lipid modifications are paralleled with a reduction in amyloid-beta (Î‘Î²) accumulation and full recovery of cognitive impairment. Omega-3 fatty acids also caused alterations in the subcellular distribution of secretases and reduced Î‘Î²-induced tau protein phosphorylation as well. Furthermore, OHDHA enhanced the survival of neuron-like differentiated cells exposed to different insults such as oligomeric Î‘Î² and N-methyl-D-aspartate-mediated neurotoxicity. In conclusion, this review focuses on the pleiotropic effects of Omega-3 fatty acids that might prove beneficial to treat AD.